Ação afirmativa para a agricultura familiar: uma avaliação da política pública implementada pelo campus Concórdia/IFC para acesso ao curso técnico em agropecuária - Marchesan, Francieli (2018)
In the last decades, there has been a considerable expansion of public policies implemented in Brazil, which aim mainly at the conquest of rights, the reduction of social inequalities and the improvement of the quality of life of the population. Many of these policies turn to education, because this area is considered fundamental to socioeconomic development, as well as the finding that educational inequalities correspond to the income inequalities and living conditions of a nation. However, regardless of the area to which they refer, all public policies must pass through the evaluation stage, since this is the instrument that allows better management of implemented programs, optimizing public resources applied, controlling government actions carried out and disseminating results to society. In this sense, the present work aims to analyze the public affirmative action policy for family agriculture implemented by the Campus Concordia of the Federal Institute of Education, Science and Technology Catarinense, to access the Technical Course in Agriculture, from a perspective of social inclusion and educational. In order to do so, a theoretical approach on public policies, its different typologies and cycle, public social policies, among them the educational ones, and a survey on the institution, course and adopted policy, objects of this study are carried out. The methodology used is based on a qualitative-quantitative research, through an institutional case study, using as instruments to collect the documentary analysis. As a result, it has been verified that the policy developed can be considered generally effective because it interferes positively in the reality of the affected population, but not efficient and not effective, for presenting results that can be considered as short as possible. However, it is important to implement policies aimed at meeting the needs of society, taking into account that even if affirmative action for family agriculture has presented less significant results, it is still positive and represents a fundamental measure for the purpose of social and educational inclusion of students coming from agricultural activity, only needing adjustments for their improvement.